Emergency postpartum hysterectomy in Sisaket Hospital: clinical characteristic and risk factors - Piyawat Angkawanich (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:To determine the incidence, indications, clinical characteristics and risk factors influencing EPH.Design: A retrospective hospital-based descriptive and case control study.Setting:Department of Obstetrics and Gynecology, Sisaket Hospital.Methods and Materials:Women who was pregnant 28 weeks gestational age or more and carried out EPH within 24 hours after delivery at Sisaket Hospital from January 2012 to June 2015 (total 26 cases) were identified from labor registration records. Their medical records were reviewed to assess the following outcomes (1) incidence of EPH (2) indications for EPH (3) clinical characteristics and risk factors associated with EPH (4) complications after EPH. Women who gave birth before (2 cases) and after (2 cases) the cases of EPH (total 104 cases ) were the control used to assess the risk factors associated with EPH.Result:During the study period, there were 17,566 deliveries at 28 weeks gestational age or more. Among them, there were 26 cases undergoing EPH. The incidence was 1.48 per 1,000 deliveries. Medical records showed that placenta adherent (65.38%) was the most common indication of EPH followed by uterine atony (26.92%) and uterine rupture (7.69%). The significant risk factors affecting EPH by multivariate logistic regression analysis were maternal age ≥ 35 years, cesarean delivery and delivery at 28-36 weeks gestational age. There were two maternal deaths after EPH. Conclusions:Clinical characteristics and risk factors associated with EPH were age ≥ 35 years, cesarean delivery and delivery at GA28-36weeks.